PENERAPAN SISTEM INFORMASI AKUNTANSI TERHADAP SISTEM PENGENDALIAN INTERNAL KAS PADA PT. DATA ENERGY INFOMEDIA - Mieftahul Jannah, (2020)
The implementation of internal control systems in every company is generally well implemented. Especially with the technology in this digital era, can facilitate the company for supervising non-operational and operational activities, such as the company's cash department. The purpose of this thesis is to determine how the implementation of accounting information systems to the internal cash control system of PT. Data Energy Infomedia. The Field Work Practices was done in 3 months, the author obtained relevant information about the implementation of accounting information systems to the internal cash control system at PT. Data Energy Infomedia. Data collections in this thesis are conducted through interviews, observation, and documentation. Data analysis was performed descriptively on the part of the parties involved in cash receipts and cash disbursements. The benefit obtained from the Practice of Field Work is to determine the implementation of accounting information systems to the cash internal control system. Based on the results of data collection from PT. Data Energy Infomedia, the company has implemented the internal control system of cash receipts and cash disbursements properly and correctly which includes relevant parts and related documents. The parts section related to cash receipts and cash disbursements include the cashier, the accounting department, and the director of administration and finance as well as documents used are invoices, proof of cash in and cash out evidences.